2020
DOI: 10.1177/2050313x20945562
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated vacuolar myelopathy: A rare initial presentation of HIV

Abstract: HIV-associated vacuolar myelopathy, or AIDS-associated myelopathy, is a rare initial presentation of HIV. One of the common HIV-associated neurocognitive disorders, HIV-associated vacuolar myelopathy presents with advanced immunosuppression in patients and is frequently associated with dementia. However, most cases are subclinical with characteristic findings identified through physical examination and/or imaging modalities. HIV-associated vacuolar myelopathy is characterized by progressive spastic paraparesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…As the condition is rare and hard to diagnose at an appropriate time due to its similar presentation to the subacute combined degeneration seen in B12 deficiency, case reports provide valuable information. In one case report of a 34-year-old man who experienced cognitive changes, spasticity, gait dysfunction, and urinary incontinence, the initiation of ART resulted in improved cognitive changes but no improvements to spasticity or urinary incontinence [ 121 ]. A case report in India in 2020 described the treatment of vacuolar myelopathy with IVIG, resulting in the resolution of spastic paresis and sensory processing disorders with a retained Babinski’s sign [ 122 ].…”
Section: Glutathione In Vacuolar Myelopathymentioning
confidence: 99%
“…As the condition is rare and hard to diagnose at an appropriate time due to its similar presentation to the subacute combined degeneration seen in B12 deficiency, case reports provide valuable information. In one case report of a 34-year-old man who experienced cognitive changes, spasticity, gait dysfunction, and urinary incontinence, the initiation of ART resulted in improved cognitive changes but no improvements to spasticity or urinary incontinence [ 121 ]. A case report in India in 2020 described the treatment of vacuolar myelopathy with IVIG, resulting in the resolution of spastic paresis and sensory processing disorders with a retained Babinski’s sign [ 122 ].…”
Section: Glutathione In Vacuolar Myelopathymentioning
confidence: 99%
“…(20) In advanced immunosuppression is more commonly reported with neurocognitive disorders especially HAD. (21) Dementia is a clinical manifestation in 4-15% of patients with HAND. (22) This study did not show a significant correlation between vitamin B12 and neurocognitive function based on MMSE or MoCA-Ina scores but some studies showed the importance of vitamin B12 in this condition, there is a methylation reaction disorder that causes neurological and psychological dysfunction.…”
Section: Research Characteristicsmentioning
confidence: 99%
“…As with HIV-associated dementia, ART is the mainstay of therapy. Although there is limited benefit in slowing progression once this condition has developed, cases of improvement have been reported 42,43 …”
Section: Direct Viral Neurologic Complications Of Hivmentioning
confidence: 99%
“…Although there is limited benefit in slowing progression once this condition has developed, cases of improvement have been reported. 42,43 COMPARTMENTALIZED CENTRAL NERVOUS SYSTEM INFECTION (CSF ESCAPE). CSF escape refers to the presence of ongoing viral replication within the CNS despite relative virologic suppression in the blood with ART use.…”
Section: Commentmentioning
confidence: 99%